2019
DOI: 10.5194/acp-19-2947-2019
|View full text |Cite
|
Sign up to set email alerts
|

Fine dust emissions from active sands at coastal Oceano Dunes, California

Abstract: Abstract. Sand dunes and other active sands generally have a low content of fine grains and, therefore, are not considered to be major dust sources in current climate models. However, recent remote sensing studies have indicated that a surprisingly large fraction of dust storms are generated from regions covered by sand dunes, leading these studies to propose that sand dunes might be globally relevant sources of dust. To help understand dust emissions from sand dunes and other active sands, we present in situ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 109 publications
(181 reference statements)
3
19
3
Order By: Relevance
“…The significantly higher sandblasting efficiency of the feldspar-quartz is in contrast with the small difference found in the PM 10 concentrations of noncoated sands (Figure 2). Field experiments on coated feldspar-quartz sand (Huang et al, 2019) showed relatively low PM 10 emissions compared to other nonsandy soils but a bit higher than those received from the noncoated feldspar-quartz sand in this study. The dust emission described for the coated feldspar-quartz sand is in general considered as low (Huang et al, 2019), and therefore, the impact of the coatings removal on the dust emission is probably small.…”
Section: 1029/2020jf005545contrasting
confidence: 56%
See 2 more Smart Citations
“…The significantly higher sandblasting efficiency of the feldspar-quartz is in contrast with the small difference found in the PM 10 concentrations of noncoated sands (Figure 2). Field experiments on coated feldspar-quartz sand (Huang et al, 2019) showed relatively low PM 10 emissions compared to other nonsandy soils but a bit higher than those received from the noncoated feldspar-quartz sand in this study. The dust emission described for the coated feldspar-quartz sand is in general considered as low (Huang et al, 2019), and therefore, the impact of the coatings removal on the dust emission is probably small.…”
Section: 1029/2020jf005545contrasting
confidence: 56%
“…Field experiments on coated feldspar-quartz sand (Huang et al, 2019) showed relatively low PM 10 emissions compared to other nonsandy soils but a bit higher than those received from the noncoated feldspar-quartz sand in this study. The dust emission described for the coated feldspar-quartz sand is in general considered as low (Huang et al, 2019), and therefore, the impact of the coatings removal on the dust emission is probably small. Thus, the difference in the sandblasting efficiency between the coated feldspar-quartz sand (green in Figure 5) and the noncoated feldspar-quartz sand (blue in Figure 5) is relatively low.…”
Section: 1029/2020jf005545contrasting
confidence: 56%
See 1 more Smart Citation
“…This suggests that much of the emitted material from dune areas is composed of previously deposited fines. The available information suggests, however, that much of this material is much finer (PM 10 , PM 2.5 ) than coarse silt (e.g., Sweeney et al, 2016; Huang et al, 2019), but the instrumentation to produce these data only measured the finer particles.…”
Section: Discussionmentioning
confidence: 99%
“…The Oceano coastal dune field of south-central California is unusual, in that it is a source of fine particulate matter (PM 10 and PM 2.5 ) that gives rise to exceedance of state and federal air-quality standards downwind (Huang et al, 2019). Oceano dune sands are mineralogically immature and are characterized by a high content (46% by mass) of feldspar grains, which may be partially weathered in this salt-rich environment, as well as clay minerals.…”
Section: Field Studies Of Dust Emissions and Abrasion From Dune Areasmentioning
confidence: 99%